Speciation and kinetic study of iron promoted sugar conversion to 5-hydroxymethylfurfural (HMF) and levulinic acid (LA)1. Issue 10 (14th October 2015) - Jiang, Yuan; Yang, Linan; Bohn, Christine M.; Li, Guannan; Han, Dong; Mosier, Nathan S.; Miller, Jeffrey T.; Kenttämaa, Hilkka I.; Abu-Omar, Mahdi M.
<x xml:space="preserve">Abstract</x> Identification of catalytic species and their contributions in iron catalyzed sugar conversion to hydroxymethylfurfural and levulinic acid.